Open incisional hernia repair with a self-gripping retromuscular Parietex mesh: A retrospective cohort study. (January 2015) - Verhelst, J.; de Goede, B.; Kleinrensink, G.J.; Jeekel, J.; Lange, J.F.; van Eeghem, K.H.A.
Abstract: Introduction : The Rives-Stoppa and component separation technique are considered to be favourable techniques in the treatment of complex incisional hernias. However, mesh-related complications like chronic pain are still a common problem after mesh repair. As a result, a new self-gripping mesh to omit suture fixation has been developed. This study aimed to evaluate the safety and feasibility of the Parietex™ Progrip self-gripping mesh in retromuscular position for the treatment of incisional hernias.Methods : Patients with incisional hernia who underwent repair between June 2012 and June 2014, using a self-gripping mesh in retromuscular position, were included in the study. All patients visited the outpatient clinic to identify postoperative complications and early recurrence.Results : A total of 28 consecutive patients with a median age of 48 years were included in the study. Twenty-two patients (79%) were diagnosed with an incisional hernia, of whom nine (32%) had a recurrence. Six patients (21%) had an incisional hernia combined with another abdominal wall hernia. The median follow-up was 12 weeks (IQR: 8–20 weeks). Twenty-three patients (82%) did not report any pain at their final outpatient clinic visit; two patients (7%) reported mild abdominal pain, and three patients (11%) had moderate abdominal pain. None of the 28 patients developed a recurrence during follow-up.Conclusion : This is the first study concerning the use of a Parietex™ Progrip mesh placed in retromuscular position. The study shows that it is a safe and feasible prosthesis in incisional hernias repair, as short-term recurrence did not occur and adverse events were limited. Highlights: Mesh in retromuscular position is a favourable technique for ventral hernias. A self-gripping mesh is feasible to place in retromuscular position without sutures. Short-term recurrence did not occur and adverse events were limited. Randomised prospective studies with long-term follow-up need to be conducted.